1970
DOI: 10.1113/jphysiol.1970.sp009278
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the cardio‐inhibitory response to brain stem ischaemia after destruction of the area postrema and the dorsal vagal nuclei

Abstract: SUMMARY1. In anaesthetized cats, in which the carotid arterial bifurcation had been denervated and the spinal cord transacted at the cervical level, reversible bradyeardia mediated by the vagus nerves was elicited by temporary arrest of the cranial circulation. Methoxamine was infused intravenously to maintain peripheral vascular resistance, and artificial ventilation was given to avert systemic asphyxia.2. The bradycardia persisted in cats subjected to one or more of the following acute surgical procedures: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

1977
1977
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 24 publications
1
4
0
2
Order By: Relevance
“…This study has confirmed and elaborated upon the long-standing observations that the primary response to cerebral ischemia consists of arterial hypertension (McDowell, 1933;Guyton, 1948;Sagawa et al, 1961;Downing et al, 1963;Miyakawa, 1966), bradycardia (McDowell, 1933Levy et al, 1968;Borison and Domjan, 1970), and apnea (Guyton, 1948;Levy et al, 1968) and that the rise in arterial pressure is due to increased peripheral resistance caused by intense vasoconstriction (Downing et al, 1963;Shimizu and Miyakawa, 1968). The vasoconstriction is primarily neurogenic and is mediated by a-adrenergic receptors.…”
Section: The Primary Cerebral Ischemic Responsesupporting
confidence: 76%
See 2 more Smart Citations
“…This study has confirmed and elaborated upon the long-standing observations that the primary response to cerebral ischemia consists of arterial hypertension (McDowell, 1933;Guyton, 1948;Sagawa et al, 1961;Downing et al, 1963;Miyakawa, 1966), bradycardia (McDowell, 1933Levy et al, 1968;Borison and Domjan, 1970), and apnea (Guyton, 1948;Levy et al, 1968) and that the rise in arterial pressure is due to increased peripheral resistance caused by intense vasoconstriction (Downing et al, 1963;Shimizu and Miyakawa, 1968). The vasoconstriction is primarily neurogenic and is mediated by a-adrenergic receptors.…”
Section: The Primary Cerebral Ischemic Responsesupporting
confidence: 76%
“…THE CEREBRAL ischemic response consists of an elevation of arterial pressure (McDowell, 1933;Guyton, 1948;Sagawa et al, 1961;Downing et al, 1963;Miyakawa, 1966), bradycardia (Anrep and Segall, 1926;McDowell, 1933;Guyton, 1948;Miyakawa, 1966;Levy et al, 1968;Borison and Domjan, 1970), and apnea (Guyton, 1948;Levy et al, 1968) elicited by interruption of the blood supply to the head. In the past, most investigations of the response have focused on its cardiovascular components (Anrep and Segall, 1926;McDowell, 1933;Guyton, 1948;Sagawa et al, 1961;Downing et al, 1963;Miyakawa, 1966;Levy et al, 1968;Borison and Domjan, 1970).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inspiratory gating mechanism was shown to operate also in the presence of brain stem ischaemia, at which time electrical stimulation of'the medullary inspiratory centre reversed the hypoxia-induced bradycardia (Borison & Domjan, 1970). This places the neuronal interaction of respiratory and cardiomotor control mechanisms downstream to the nucleus of the solitary tract, very probably in the reticular formation (Biscoe & Sampson, 1970).…”
Section: Methods Of Evoking the Carotid Sinus Respiratory Reflexmentioning
confidence: 99%
“…An outstanding example of centrally co-ordinated cardiorespiratory behaviour is the generation of sinus arrhythmia whereby the act of inspiration silences vagal discharge to the heart (Eckberg, Kifle & Roberts, 1980;Spyer, 1981). The inspiratory gating mechanism was shown to operate also in the presence of brain stem ischaemia, at which time electrical stimulation of'the medullary inspiratory centre reversed the hypoxia-induced bradycardia (Borison & Domjan, 1970). This places the neuronal interaction of respiratory and cardiomotor control mechanisms downstream to the nucleus of the solitary tract, very probably in the reticular formation (Biscoe & Sampson, 1970).…”
Section: Role Of the Vagus Nerves In The Carotid Sinus Reflex Respiramentioning
confidence: 99%